Life Cycle Assessment of Bridge Infrastructure Materials - Iman Niat Kurniawati Gulo; Arinta Primandini Aulia (Momentum International Journal of Civil Engineering (MIJCE), 2025)
The environmental impact of infrastructure development has become a critical concern in sustainable engineering practices, particularly in large-scale projects such as bridge construction. This study presents a comprehensive life cycle assessment (LCA) of commonly used bridge infrastructure materials—including concrete, steel, and composite systems—across their entire lifespan from raw material extraction to end-of-life disposal. Using ISO 14040 and ISO 14044 standards as the methodological foundation, the assessment evaluates global warming potential (GWP), embodied energy, and environmental toxicity across four bridge design scenarios. Data were collected from regional suppliers and international LCA databases to ensure accuracy and relevance. Results indicate that material selection significantly influences the overall carbon footprint and energy consumption of bridge structures. Steel-intensive designs showed higher GWP during production but offered advantages in recyclability, whereas concrete exhibited lower initial emissions but higher long-term maintenance impacts. Composite systems demonstrated potential for both structural efficiency and reduced environmental impact when optimized. The study emphasizes the importance of early-stage material decisions and supports the integration of LCA tools into bridge design workflows to enhance sustainability in civil infrastructure development.